2000
DOI: 10.1161/01.str.31.5.1024
|View full text |Cite
|
Sign up to set email alerts
|

Home or Hospital for Stroke Rehabilitation? Results of a Randomized Controlled Trial

Abstract: Background and Purpose-We wished to examine the effectiveness of an early hospital discharge and home-based rehabilitation scheme for patients with acute stroke. Methods-This was a randomized, controlled trial comparing early hospital discharge and home-based rehabilitation with usual inpatient rehabilitation and follow-up care. The trial was carried out in 2 affiliated teaching hospitals in Adelaide, South Australia. Participants were 86 patients with acute stroke (mean age, 75 years) who were admitted to hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
153
1
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(161 citation statements)
references
References 37 publications
3
153
1
4
Order By: Relevance
“…Holmqvist et al explicitly used an MMSE score of 23 in their inclusion criteria 10 and two others reported average admission scores of 28 and 21, respectively. 6,15 In these three studies, the mean score on admission was 24/30. Similar to BI, the study with the widest dispersion of admission MMSE scores was Rudd et al, 15 in which 1 standard deviation from the mean ranged from 14 to 28.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Holmqvist et al explicitly used an MMSE score of 23 in their inclusion criteria 10 and two others reported average admission scores of 28 and 21, respectively. 6,15 In these three studies, the mean score on admission was 24/30. Similar to BI, the study with the widest dispersion of admission MMSE scores was Rudd et al, 15 in which 1 standard deviation from the mean ranged from 14 to 28.…”
Section: Discussionmentioning
confidence: 90%
“…In total, eight studies were included for further assessment. 6,[9][10][11][12][13][14][15] A summary of the programs explored in the studies of a team coordinated and delivered ESD program is provided in Table 1. All teams included a physiotherapist (PT) and occupational therapist (OT) and most included access to a speech language pathologist (SLP).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have indicated that an extended pro gramme in the community, provided by a dedicated team could result in patients being discharged earlier from hospital (Anderson et al 2000;Bautz Holter et al 2002;Donnelly et al 2004;Indredavik et al 2000;Mayo et al 2000). This approached was developed as the home setting, is conducive to relearning skills post stroke (Anderson et al 2000;Bautz Holter et al 2002;Donnelly et al 2004;Indredavik et al 2000;Mayo et al 2000). Unfortunately this type of extended ser vices is non existent in under resourced rehabilitation settings such as in the Western Cape.…”
mentioning
confidence: 99%
“…Several studies on different models for discharging and follow-up for stroke patients have been performed with varying effect, and there is still no consensus concerning care of stroke patients after discharge (Holmqvist et al, 1998;Anderson et al, 2000;Ytterberg et al,2000). "Early supported discharge'' is one of the settings studied in other countries.…”
Section: Discharge Program and Follow Up Services After Inpatient Strokmentioning
confidence: 99%